Role of Effective Internal Control Structure in Achievement of Targeted Success in Businesses - Turedi, Hasan; Celayir, Duygu (European Scientific Journal, ESJ, 2018)
Due to economic relations evolving over time, technology and changing business environments, the way in which one of the management functions, “control”, is executed has undergone a number of changes. Accordingly, the management of a business has become unable to control operations directly, making it a necessity for businesses to obtain timely and reliable data for a number of purposes, including protecting assets, and eliminating or minimizing errors and frauds. Internal control structures, formed within the business to serve this purpose, have become more relevant in terms of protecting business assets, identifying the way operations are executed and ensuring execution of operations at the desired level of efficiency. Internal control is defined as a structure in businesses which is directed by board of directors, managers and employees, aims to ensure effectiveness and efficiency of operations, reliability of the financial reporting system, and compliance with laws, and is designed to provide reasonable assurance in these aims. Depending on the position they assume, officials at every level have responsibilities in the context of ensuring effective and efficient execution of the internal control structure in businesses, and accordingly, of corporate management, and attaining expected goals. This study will examine development of an effective internal control structure in terms of attaining expected success by businesses and the impact thereof on the business.